Effect of aqueous extract of Ginger plant Root on some parameters of fertility in local Male Rabbits - إبراهيم, نهلة; علو, لينا (Latakia University Journal -Biological Sciences Series, 2021)
The present study aimed to evaluate the effect of roots extract of ginger plant on some fertility parameters in the local male rabbits.15 adult male rabbits divided into three groups of five each were used. . Group 1 (control) was received normal food and water for a period of ten weeks while group 2 and three received orally a dose of aqueous plant extract (100 mg/b.w) and 200 mg/kg/b.w. respectively, daily for ten weeks also. In the end of experience, blood samples were taken for testosterone concentration in blood serum, and testis were excised and their weights and lengths were measured. Sperm count in the semen taken from the caudle epididymis was done using Hemocytometer. In addition, the motility and morphological abnormalities of sperms were assessed. The results showed a significant increase in the concentration of testosterone hormone in the experimental groups (P˂0.01) comparing to the control. In addition, a significant increase in the mean of testis weights and lengths (P˂0.01) was also noted. The study also showed a significant increase in the sperm count (P˂0.01), and also in their motility in the experimental groups (P˂0.01) and a decrease in the morphological abnormalities comparing to control group.